2014
DOI: 10.1681/asn.2013070742
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Biomarkers of AKI and Mortality 3 Years after Cardiac Surgery

Abstract: Urinary biomarkers of AKI provide prognostic value for in-hospital outcomes, but little is known about their association with longer-term mortality after surgery. We sought to assess the association between kidney injury biomarkers and all-cause mortality in an international, multicenter, prospective long-term follow-up study from six clinical centers in the United States and Canada composed of 1199 adults who underwent cardiac surgery between 2007 and 2009 and were enrolled in the Translational Research in Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
136
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 154 publications
(144 citation statements)
references
References 28 publications
7
136
0
1
Order By: Relevance
“…Before surgery, for example, we had already observed significant differences in IL-6 among patients who went on to develop both AKI and severe AKI. Our findings build on our previous work that has provided both diagnostic and prognostic information for clinical prediction models [26][27][28][29][30][31][32][33][34] and demonstrates that these cytokines may serve as prognostic biomarkers for perioperative outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…Before surgery, for example, we had already observed significant differences in IL-6 among patients who went on to develop both AKI and severe AKI. Our findings build on our previous work that has provided both diagnostic and prognostic information for clinical prediction models [26][27][28][29][30][31][32][33][34] and demonstrates that these cytokines may serve as prognostic biomarkers for perioperative outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, Coca et al 1 showed that several biomarkers of AKI measured in the perioperative period after adult cardiothoracic surgery correlated with long-term risk of mortality. In their follow-up of 1199 adults from the Translational Research Investigating Biomarker Endpoints in Acute Kidney Injury (TRIBE-AKI) cohort, Coca et al 1 showed that, compared with the first tertiles, the third tertiles of peak biomarker percentages of urine neutrophil gelatinase associated lipocalin, interleukin-18, kidney injury molecule-1, liver fatty acid binding protein, and urine albumin were all associated with a significantly increased risk of mortality in those subjects who developed postoperative AKI.…”
Section: Risk Of Death or Dialysis Increased Atmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Over the last decade, there has been intense investigation of biomarkers of kidney injury in an attempt to complement and augment the diagnostic abilities of current measures of kidney function. 8 To date, little is known about the relationship between these novel biomarkers and long-term outcomes, 9,10 with only one largescale multicenter investigation linking some biomarkers collected around the time of AKI with long-term mortality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These datasets were linked using unique encoded identifiers and analyzed at the Institute for Clinical Evaluative Sciences (ICES). Full study details were previously described 34, 35, 36…”
Section: Methodsmentioning
confidence: 99%